2000
DOI: 10.1524/ract.2000.88.8.453
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and desorption kinetics of Np(V) on magnetite and hematite

Abstract: Sorption kinetics of Np(V) on magnetite and hematite were investigated, and a sequential desorption method was applied to investigate changes in the chemical form of Np sorbed according to the amount of time they were in contact with the Np solution. It was found that the sorption process consists of fast sorption and slow sorption which reaches equilibrium in 1 h. According to the desorption results, it was conjectured (i) that fast sorption is attributable to sorption on/into the surface and non-crystalline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
4
10
0
Order By: Relevance
“…It was established that Np(V) sorption by ␣-Fe 2 O 3 and ␣-FeOOH is described by two-steps process: rapid sorption on external surface of the colloids and the slow diffusion to internal micropores. These results are consistent with previously reported data [19,20].…”
Section: Sorption Experimentssupporting
confidence: 94%
“…It was established that Np(V) sorption by ␣-Fe 2 O 3 and ␣-FeOOH is described by two-steps process: rapid sorption on external surface of the colloids and the slow diffusion to internal micropores. These results are consistent with previously reported data [19,20].…”
Section: Sorption Experimentssupporting
confidence: 94%
“…The dominant aqueous NpO 2 + sorbed onto ferrihydrite surface to form NpO 2 (OH) 0 surface complex. Recent studies on the sorption of Np(V) onto hematite [110][111][112][113], goethite [112] and magnetite [113] are in agreement with the previous results for ferrihydrite. The sorption behavior of Np(V) to hematite under aerobic and anaerobic conditions was not noticeably different, because the Np(V) species onto hematite was not reduced [110].…”
Section: Distribution Coefficient and Sorption Percentagesupporting
confidence: 90%
“…Results from previous Np(V)-iron (oxyhydr)oxide sorption studies under aerobic conditions indicate a fast initial metal uptake in the order of minutes to hours followed by slower metal sorption rates over days to weeks (Nakayama and Sakamoto, 1991;Kohler et al, 1999;Nakata et al, 2000;Jerden and Kropf, 2007). Neptunium desorption experiments with Fe-(oxyhydr)oxides have been performed at the same chemical solution conditions as during adsorption (Keeney-Kennicutt and Morse, 1984), after controlled changes in solution pH (Nakayama and Sakamoto, 1991;Jerden and Kropf, 2007), or with various types of extraction solutions (Keeney-Kennicutt and Morse, 1984;Nakata et al, 2000;Nakata et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Neptunium desorption experiments with Fe-(oxyhydr)oxides have been performed at the same chemical solution conditions as during adsorption (Keeney-Kennicutt and Morse, 1984), after controlled changes in solution pH (Nakayama and Sakamoto, 1991;Jerden and Kropf, 2007), or with various types of extraction solutions (Keeney-Kennicutt and Morse, 1984;Nakata et al, 2000;Nakata et al, 2002). Nakata et al (2000) found that after Np was sorbed to hematite over one week, 24% remained sorbed after sequential desorption steps with 1 M KCl and 0.1 M K 2 C 2 O 4 . Keeney-Kennicutt and Morse (1984) observed a Np fraction of approximately 66% desorbed from goethite in deionized water and natural seawater solutions after two hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation